PENILAIAN PSIKOMOTOR PENDIDIKAN AGAMA ISLAM JENJANG SEKOLAH DASAR - Ido Nardaullah; Devi Herdianti; Fitri Hilmiyati; Enung Nugraha (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the concept, stages, and implementation of psychomotor assessment in Islamic Religious Education (PAI) learning at the elementary school level. This research employs a library research method by reviewing various literature related to psychomotor theory, learning evaluation techniques, and the implementation of the Merdeka Curriculum. The results show that psychomotor assessment plays an essential role in measuring students’ skills in applying Islamic values through practical activities such as reciting the Qur’an, performing ablution, and conducting prayer. Psychomotor assessment can be conducted through observation, performance tests, projects, and portfolios using instruments such as checklists and rating scales. The psychomotor domain includes five skill levels: imitation, manipulation, precision, articulation, and naturalization. The implementation of this assessment helps teachers objectively evaluate students’ spiritual skills and religious practices, supporting the development of learners who are faithful, virtuous, and aligned with the values of the Pancasila Student Profile.